Creating the cultures of the future: cultural strategy, policy and institutions in Gramsci. Part two: Cultural strategy and institutions in Gramsci’s early writings and political practice - Merli, Paola (Taylor & Francis, 2013)
In this article, I consider Gramsci’s pre-prison writings and political practice in relation to questions of cultural strategy and institutions. I argue that the analysis of these early texts, which were written in the years in which Gramsci was active in party organisation and leadership, is fundamental not only for understanding the nature of Gramsci’s early and continued involvement with questions of cultural strategy and institutions, but also as a key for interpreting cultural policy themes that he later developed in the prison notebooks, and which originated in earlier debates.